1979
DOI: 10.1029/jb084ib10p05643
|View full text |Cite
|
Sign up to set email alerts
|

Seismic refraction and reflection measurements in the Middle America Trench offshore Guatemala

Abstract: Seismic refraction, 24-fold, common-depth-point reflection and magnetic field profiles were obtained during the summer of 1977 on the inner slopes of the Middle America Trench off Guatemala. In addition, piston cores and dredge samples were collected along the midslope region. Five unreversed refraction profiles between 20-and 80-km length were recorded by Texas ocean bottom seismographs using air guns, Maxipulse, and conventional explosives as the sound sources. Travel time-distance curves based on first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 12 publications
3
45
0
Order By: Relevance
“…Gravity and magnetic data, particularly a magnetic high parallel to the trench-slope break, are consistent with the presence of high-density crustal rocks at shallow depths, and indicate that these rocks may be an extension of mid-Tithonian-upper Santonian ophiolitic rocks exposed in coastal Costa Rica (Woodcock, 1975;Couch 1976;Couch and Woodcock, 1981). The recovery of clasts of serpentinite, basalt, and chert in cores and dredges along the trench slope supports this interpretation (Ibrahim et al, 1979).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Gravity and magnetic data, particularly a magnetic high parallel to the trench-slope break, are consistent with the presence of high-density crustal rocks at shallow depths, and indicate that these rocks may be an extension of mid-Tithonian-upper Santonian ophiolitic rocks exposed in coastal Costa Rica (Woodcock, 1975;Couch 1976;Couch and Woodcock, 1981). The recovery of clasts of serpentinite, basalt, and chert in cores and dredges along the trench slope supports this interpretation (Ibrahim et al, 1979).…”
Section: Introductionsupporting
confidence: 61%
“…In contrast, coring recovered serpentinite as the sole basement rock at Holes 566, 566A, 566C, and 570; serpentinite in blocks and between units of basalt and gabbro in Hole 567A; and gabbro and basalt alone in Hole 569A (site chapters, this volume). Furthermore, the common association reported in dredge and piston core samples is serpentinite, basalt, and chert (Ibrahim et al, 1979); gabbro is notably lacking from these sets of samples. The coarser-grained samples from Leg 84 are predominantly altered, massive gabbro or diabase, rather than cumulate-textured gabbros.…”
Section: Discussionmentioning
confidence: 99%
“…Ladd et al (1978) and Ibrahim et al (1979) showed that seismic refraction and reflection interval velocities within the Figure 5. The imbricate underthrust accretionary model of Seely et al (1974).…”
Section: I-i-i-ihr23rmentioning
confidence: 99%
“…Magnetic and gravity data indicate that a basement high follows discontinuously the continental shelf edge from the Gulf of Tehuantepec off Mexico southward to the Nicoya Peninsula off Costa Rica where an Early Cretaceous ophiolite complex crops out (Dengo, 1962;Couch and Woodcock, 1981;Lund-berg, 1982). Seismic refraction studies off Guatemala indicate two landward-dipping units with velocities and thicknesses appropriate for oceanic crust (Ibrahim et al, 1979). Sediments drilled on the shelf edge by Exxon almost immediately above acoustic basement were deposited at abyssal depths, indicating that thin, probably oceanic crust forms basement (Seely, 1979).…”
Section: Introductionmentioning
confidence: 99%